Biased labels: An experimental study of language and stigma among individuals in recovery and health professionals. (3rd July 2019) - Ashford, Robert D.; Brown, Austin M.; McDaniel, Jessica; Curtis, Brenda
Abstract: Background : Labels such as "addict" and "substance abuser" have been found to elicit implicit and explicit stigma among the general public previously. The difference in the levels of this bias among individuals in recovery and those employed in the health profession has not yet been identified, however. The current study seeks to answer this question using measures of implicit bias. Methods : A subset sample ( n = 299) from a previously completed study ( n = 1288) was selected for analysis. Mixed-model ANOVA tests were completed to identify variance between d-prime automatic association scores with the terms "addict" and "substance abuser" among individuals in recovery and those identified as working in the health professions. Results : Individuals in recovery did not have lower negative associations with either term, whereas individuals employed as health professionals had greater negative associations with the term "substance abuser" but did not have greater negative associations with the term "addict." Conclusions : Results provide further evidence that previously identified stigmatizing labels have the potential to influence medical care and medical practitioner perceptions of individuals with substance use disorders and should be avoided. Further exploration into the role negative associations derived from commonly used labels have in the individual recovery process is needed to draw appropriate recommendations.